Caste, Inequality, and Poverty in India - Vani K. Borooah (Review of Development Economics, 9(3), 399-414, 2005, 2005)
This paper analyses inequality and poverty in India within the context of caste-based discrimination. It does so by decomposing the difference between (caste) Hindu and Scheduled Caste (SC) and Scheduled Tribe (ST) households in: their average household incomes; their probabilities of being in different income percentiles; their probabilities of being at different levels of poverty into: a "discrimination effect", which stems from the fact that a household's income level, into which its (income-generating) profile Translates, depends on whether it is SC/ST; an "attributes (or residual) effect" which stems from the fact that there are systematic differences between SC/ST and Hindu households in their (income-generating) profiles. The results, based on unit record data for 28,922 households, showed that at least one-third of the average income/probability differences between Hindu and SC/ST households was due to the "unequal treatment" of the latter.